2017
DOI: 10.1016/j.injury.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Mini-Nutritional Assessment short and long form and serum albumin as prognostic indicators of hip fracture outcomes

Abstract: Introduction: Malnutrition is common among older hip fracture patients and associated with adverse outcomes. We examined Mini Nutritional Assessment short (MNA-SF) and long form (MNA-LF) and serum albumin as prognostic indicators of mobility, living arrangements and mortality after hip fracture.Methods: Population-based prospective data were collected on 594 hip fracture patients aged 65 and over. MNA-SF, MNA-LF and serum albumin were assessed on admission. Outcomes were poorer mobility; transfer to more assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 30 publications
5
68
0
2
Order By: Relevance
“…Of the patients at risk of malnutrition and with normal nutritional status respectively 21% and 10% died within four months. Similar results have been reported earlier (10,11,18,26). No significant difference could be seen between groups when using NRS2002.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Of the patients at risk of malnutrition and with normal nutritional status respectively 21% and 10% died within four months. Similar results have been reported earlier (10,11,18,26). No significant difference could be seen between groups when using NRS2002.…”
Section: Discussionsupporting
confidence: 90%
“…This indicates the patient's overall condition and high scores predict a greater number of comorbidities and mortality after hip fracture treatment (24). Over half of the malnourished patients had memory disorder but only 22% of the patients with normal nutritional status, thereby corroborating earlier reports (5,11).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Previous studies have demonstrated that the MNA-SF and the GNRI were more suitable for assessing nutritional status than serum albumin [13,33]. In addition, the GNRI and MNA-SF had better performance in predicting adverse outcomes than serum albumin [34,35]. Thus, more comprehensive and systematic nutritional screening methods, such as the GNRI and the MNA-SF, are needed to evaluate nutritional status or nutrition-related complications among surgical patients.…”
Section: Discussionmentioning
confidence: 99%
“…Depression was assessed with the 5-point Geriatric Depression Scale (GDS) 22–24. The Mini-Nutritional Assessment Short Form (MNA-SF),18 25–28 Nestlé (https://www.mna-elderly.com/) was used to assess nutritional risk. Because of the high prevalence of oedema, only body mass index and not calf circumference was used for the MNA-SF.…”
Section: Methodsmentioning
confidence: 99%